Enantioselective Intramolecular Copper‐Catalyzed Borylacylation. (21st September 2018) - Whyte, Andrew; Burton, Katherine I.; Zhang, Jingli; Lautens, Mark
Abstract: An enantioselective copper‐catalyzed intramolecular borylacylation is reported. The reaction proceeds through an initial enantioselective borylcupration of the styrene, followed by a nucleophilic attack on the tethered carbamoyl chloride. The products, chiral borylated 3, 3‐disubstituted oxindoles, were generated in excellent yields and enantioselectivities. The versatile carbon–boron bond provides a platform for a wide array of diversification.